Automated Identification of Diabetic Retinopathy Stages in Digital Fundus Image using CDR and Micro aneurysms (International Journal of Engineering and Computer Science, 2017)
Diabetic retinopathy (DR) and glaucoma are the commonest complications of diabetes and is one of the leading causes of blindness. Early detection of occurrence of DR can greatly help in effective treatments. Very effective treatments are available and are optimally used when retinopathy is detected early. For this reason screening programs for early detection of retinopathy is essential part. The retinal fundus photographs are the main resources for screening of DR. In this work we tried to locate the eye optic disc and optic cup using k-means algorithm, morphological operation and watershed transform. Segmented optic disc and cup are then used to compute the cup to disc ratio for DR screening, for grading the disease we use micro aneurysms. Micro aneurysms are the clinical sign of DR they appear small red dots on retinal fundus images, their detection can be used to grade the DR in different stages.